Soft Power of Higher Education as a Global Leadership Factor - N. L. Antonova; A. D. Sushchenko; N. G. Popova (Obrazovanie i Nauka)
Introduction. The main objectives of foreign policy of any state include the extension of its influence in the international arena. In the era of information and knowledge, one of the most effective tools for this task is soft power of education. In this respect, education is seen as a promising soft power instrument, which long-term character allows a country to promote not only its cultural, scientific and technological achievements, but also its cultural values and norms of social organisation. Today, universities are also seeking to strengthen their positions in global education rankings, which are used to define the status and reputation of a particular university in the global market of educational services. This ranking serves as a guide for future students and their parents, when choosing a prestigious education location and when developing individual career paths.The aims of the present research are the following: to analyse soft power of higher education as a soft power mechanism, which allows a country to achieve and maintain leadership positions in the international arena; to specify conditi ons, factors and barriers that determine the position of universities in global ranking systems.Methodology and research methods. The methodological framework is based on the concept of soft power and the theory of internationalisation of higher education. The empirical study was conducted following the tradition of qualitative sociological research. In 2018, a series of semi-structured interviews was conducted among Ural Federal University employees, whose responsibilities were related to the promotion of the university on the global educational market. The Ural Federal University (UrFU) can be considered representative in terms of practices aimed at attracting foreign students to the BRICS countries. In addition, UrFU is a place where the concept of a network BRICS University was realised in 2017. A total of 5 expert interviews were conducted. The collected data were analysed in the context of the World Bank statistics on the money spent by the BRICS countries on education and R&D during the 1999–2015 period (% of GDP), as well as the data provided by the QS World University Rankings – 2019 to analyse the reputation of BRICS universities.Results and scientific novelty. The case study of Ural Federal University allowed the authors to consider the specific practices of BRICS zones for attracting foreign students. The authors analysed the specifics of actions taken by a university to promote its international leadership positions in the international space on the example of students from China. It is shown that the role of global ranking systems (institutional and faculty) in the choice of a university is steadily growing. At the same time, factors determining the attractiveness of the Ural Federal University for foreign students, in particular for Chinese students, include a reasonable level of tuition, the quality of the education and the formed ethnic social networks. For them, the Russian education is expected to be a factor in achieving a higher social status in their home countries. This demonstrates the effective role of education as a soft power instrument, although in the long-term perspective. The authors identified a number of findings concerning the barriers faced by Russian universities on the way to recognising them as global actors of higher vocational education. It is possible to enter the Top 500 best world universities; however, the task of maintaining the achieved position in global rankings is more complicated and cannot be completed without a steady increase in the performance over several years. A world-class university should attract gifted youth, qualified teachers and researchers. The reduction in the number of talented people and research results leads to the loss of geopolitical mission by the educational organisation. Inadequate funding may prevent universities from breakthrough and sustainable improvement of their reputation.Practical significance. The research findings might be useful for managers of higher education and for strategists involved in positioning and making forecasts of educational institutions development. Also, the present findings can be applied by specialists engaged in the issues of educational policy, distribution of public investments, as well as the issues of international interaction and competition between states in order to realise national interests and support national economy in the country in the long term.